Implementation Search Engine Optimization (SEO) to Improve Marketing F&B Industry - Carola Basuki; Chairani Putri Pratiwi; Rizka Astari Rahmatika (bit-Tech, 2023)
In new era digital now, internet is the important think for various activities including in the process to improve business promotion. One way to increase promotion through online is to improve digital marketing strategies using Search Engine Optimization (SEO) techniques. The aim of this research is to implementation SEO to improve digital marketing in F&B industry. Developing method that used are On Page and Off Page SEO to optimize the search engine. The Researcher using literature analysis and deep interview to get the data from SMEs in F&B Industry. To create the implementation of SEO, the researcher undertakes case studies from SMEs in F&B Industry who already run the business and need to improve the Digital Marketing through SEO. However, it is important to note that SEO optimization  is  not  a  one-time  task  but  rather  an  ongoing  process.  It  requires  constant attention and effort to maintain high search engine rankings and ensure the continued success of online business. Beside website, to improve the business promotion the researcher also use tools in Google Business and E-Commerce to optimize the SEO.The finding suggest that the implementation of Search Engine Optimization can make impact for improvement in visibility search engines, attract more visitors, and ultimately drive business growth in the area Google Business, E-Commerce and website owned by SMEs F&B Industry. It is important to remain vigilant in implementing SEO techniques to maintain high search engine rankings and ensure the continued success of SMEs online business.